+0  
 
-1
36
1
avatar+199 

For functions 

f ( x) = x − 1

  and  

g ( x) = 4x2 + 3x − 5,

  find the following. ( Simplify your answers completely.)

(a)

( f  · g ) (x) = 

 

(b)

( f  · g ) (−2) = 

 

For functions 

f ( x) = 7x − 8

  and  

g ( x) = 7x + 8,

  find the following. ( Simplify your answers completely.)

(a)

( f  · g ) (x) = 

 

(b)

( f  · g ) (−2 ) =

 Apr 18, 2020
 #1
avatar+20810 
+1

I'm assuming that "·" means "multiplication", not "composition".

 

f(x)  =  x - 1          g(x)  =  4x2 + 3x - 5

 

(f · g)(x)  =  f(x) · g(x)  =  (x - 1) · (4x2 + 3x - 5)

                                   =  (x)(4x2) + (x)(3x) - (x)(5) + (-1)(4x2) + (-1)(3x) - (-1)(5)

                                   =  4x3 + 3x2 - 5x - 4x2 - 3x + 5

                                          =   4x3 - x2 - 8x + 5

(f · g)(-2)  =  4(-2)3 - (-2)2 - 8(-2) + 5  =  -15

 

The next problem is like this problem

 Apr 18, 2020

37 Online Users

avatar
avatar
avatar
avatar